2021
DOI: 10.7759/cureus.15113
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Duodenal Ulcers Among Dyspeptic Patients

Abstract: Introduction: Dyspepsia is a common presenting complaint of various upper gastrointestinal disorders. Duodenal ulcer is one of the rare endoscopic findings in patients with dyspepsia, but it can present with upper gastrointestinal bleed. The aim of this study was to determine the frequency of duodenal ulcers among dyspeptic patients undergoing esophagogastroduodenoscopy (EGD).Subject and methods: All patients who fulfilled the inclusion criteria were recruited during the period of six months, i.e., from July t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Other less frequently implicated risk factors for PUD include genetics, stress, diet, smoking and alcohol [ 16 , 17 ]. Global reports indicated that H. pylori infection rate among PUD patients was 14–21% in the United States, 60–70% in Asia, and 70–90 in sub-Saharan Africa [ 4 , 5 , 7 , 18 23 ]. There was no recent document on H. pylori infection rate among PUD patients in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Other less frequently implicated risk factors for PUD include genetics, stress, diet, smoking and alcohol [ 16 , 17 ]. Global reports indicated that H. pylori infection rate among PUD patients was 14–21% in the United States, 60–70% in Asia, and 70–90 in sub-Saharan Africa [ 4 , 5 , 7 , 18 23 ]. There was no recent document on H. pylori infection rate among PUD patients in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the prevalence of PUD remains high and is increasing year by year in the adolescent population. According to previous studies, the current prevalence of PUD is about 0.2% to 0.5% in Western countries, 2% to 3% in Asian countries (4), and 24-28% in sub-Saharan African populations (5)(6)(7). It is estimated that 15,000 people die from PUD each year, which indicates that PUD still affects human health to a large extent.…”
Section: Introductionmentioning
confidence: 99%